Changes in nature's balance sheet: model-based estimates of future worldwide ecosystem services - Alcamo, Joseph; van Vuuren, Detlef; Ringler, Claudia; Cramer, Wolfgang; Masui, Toshihiko; Alder, Jacqueline; Schulze, Kerstin (Resilience Alliance, Inc., 2005)
Four quantitative scenarios are presented that describe changes in worldwide ecosystem services up to 2050–2100. A set of soft-linked global models of human demography, economic development, climate, and biospheric processes are used to quantify these scenarios. The global demand for ecosystem services substantially increases up to 2050: cereal consumption by a factor of 1.5 to 1.7, fish consumption (up to the 2020s) by a factor of 1.3 to 1.4, water withdrawals by a factor of 1.3 to 2.0, and biofuel production by a factor of 5.1 to 11.3. The ranges for these estimates reflect differences between the socio-economic assumptions of the scenarios. In all simulations, Sub-Saharan Africa continues to lag behind other parts of the world. Although the demand side of these scenarios presents an overall optimistic view of the future, the supply side is less optimistic: the risk of higher soil erosion (especially in Sub-Saharan Africa) and lower water availability (especially in the Middle East) could slow down an increase in food production. Meanwhile, increasing wastewater discharges during the same period, especially in Latin America (factor of 2 to 4) and Sub-Saharan Africa (factor of 3.6 to 5.6) could interfere with the delivery of freshwater services. Marine fisheries (despite the growth of aquaculture) may not have the ecological capacity to provide for the increased global demand for fish. Our simulations also show an intensification of present tradeoffs between ecosystem services, e.g., expansion of agricultural land (between 2000 and 2050) may be one of the main causes of a 10%–20% loss of total current grassland and forest land and the ecosystem services associated with this land (e.g., genetic resources, wood production, habitat for terrestrial biota and fauna). The scenarios also show that certain hot-spot regions may experience especially rapid changes in ecosystem services: the central part of Africa, southern Asia, and the Middle East. In general, the scenarios show a positive balance of increasing services, especially in developing countries, and a negative balance of increasing risks and tradeoffs of services. The challenge, then, is dealing with these risks so as to avoid a future curtailment of ecosystem.